Why stand-up matters how comedians manipulate and influence - Quirk, Sophie (London Bloomsbury Methuen Drama, 2015)
Funny, lively and unpredictable, stand-up comedy is above all a medium to be enjoyed. Popular as a good night out and packing the TV schedules, stand-up permeates British society and culture. But ubiquitous though it is, we are generally reluctant to consider stand-up's social consequences. When comedians offend we seem ready to consider the potential for stand-up to do some wider harm, yet we rarely consider the good that stand-up might do. This book looks at the social and political impact of stand-up comedy in both its positive and negative forms. It demonstrates how comedy audiences allow themselves to be manipulated, and the potential harm - and material benefits - that may arise from 'just' being funny.
Joking is Manipulation -- Why Comedians Need Manipulation -- Safe Space: From Manipulation to Influence -- The Tools of Manipulation -- A Manipulative Environment -- Manipulating Responses -- Comic Licence and Manufacturing Consensus -- Persona and Status -- Efficacy and Influence -- Is Stand-up Comedy an Appropriate Medium for Debate? -- How Stand-up Matters -- Conclusion: Can Stand-up Change the World?
Includes bibliographical references (pages 233-242) and index.
Keywords: Stand-up comedy -- Social aspects; Stand-up comedy -- Political aspects